2020
DOI: 10.3844/ajbbsp.2020.451.461
|View full text |Cite
|
Sign up to set email alerts
|

A Polysaccharide-Rich Fraction Derived from Oviductus ranae with Antioxidant and Immunomodulatory Potentials

Abstract: and Yang Zhang. This open access article is distributed under a Creative Commons Attribution (CC-BY) 3.0 license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Modern pharmaceutical studies confirmed that OR possesses various functions relating to traditional uses, such as immune-enhancing properties, antioxidant and anti-fatigue activities. OR comprise several nutrients and bioactive ingredients with proteins the highest content of over 50% in most cases (Yu et al, 2020;Zhang et al, 2019a-b). Thus in previous work, the antioxidant and anti-fatigue potentials of Proteins from OR (POR) were explore and noted that the in vivo antioxidant capacity of POR weighs on the in vitro counterpart, which indicated that the underlying antioxidant activity-contributed constituents of POR would be the digestive products in the gastrointestinal tract (Zhang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmaceutical studies confirmed that OR possesses various functions relating to traditional uses, such as immune-enhancing properties, antioxidant and anti-fatigue activities. OR comprise several nutrients and bioactive ingredients with proteins the highest content of over 50% in most cases (Yu et al, 2020;Zhang et al, 2019a-b). Thus in previous work, the antioxidant and anti-fatigue potentials of Proteins from OR (POR) were explore and noted that the in vivo antioxidant capacity of POR weighs on the in vitro counterpart, which indicated that the underlying antioxidant activity-contributed constituents of POR would be the digestive products in the gastrointestinal tract (Zhang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%